تكنولوجيا المبادلات الحرارية وتطبيقاتها في هندسة المبادلات الحرارية - عمير عابدين مصطفى (المجلة العربية للعلوم و نشر الأبحاث, 2015)
Over the years, all parts of a commercial refrigerator, such as the compressor, heat exchangers, refrigerant, and packaging, have been improved considerably due to the extensive research and development efforts carried out by academia and industry. However, the achieved and anticipated improvement in conventional refrigeration technology are incremental since this technology is already nearing its fundamentals limit of energy efficiency is described is ‘magnetic refrigeration’ which is an evolving cooling technology. The word ‘green’ designates more than a colour. It is a way of life, one that is becoming more and more common throughout the world. An interesting topic on ‘sustainable technologies for a greener world’ details about what each technology is and how it achieves green goals. Recently, conventional chillers using absorption technology consume energy for hot water generator but absorption chillers carry no energy saving. With the aim of providing a single point solution for this dual purpose application, a product is launched but can provide simultaneous chilling and heating using its vapour absorption technology with 40% saving in heating energy. Using energy efficiency and managing customer energy use has become an integral and valuable exercise. The reason for this is green technology helps to sustain life on earth. This not only applies to humans but to plants, animals and the rest of the ecosystem. Energy prices and consumption will always be on an upward trajectory. In fact, energy costs have steadily risen over last decade and are expected to carry on doing so as consumption grows. Refrigerants such as hydrochloroflurocarbons (HCFCs) are present in the ground source heat pump (GSHP) systems and can pose a threat to the environment through beingtoxic, flammable or having a high global warming potential.